Performance Contracting in After-Sales Service Supply Chains - Kim, Sang-Hyun; Cohen, Morris A.; Netessine, Serguei (Management Science, 2007)
Performance-based contracting is reshaping service support supply chains in capital-intensive industries such as aerospace and defense. Known as “power by the hour” in the private sector and as “performance-based logistics” (PBL) in defense contracting, it aims to replace traditionally used fixed-price and cost-plus contracts to improve product availability and reduce the cost of ownership by tying a supplier's compensation to the output value of the product generated by the customer (buyer). To analyze implications of performance-based relationships, we introduce a multitask principal-agent model to support resource allocation and use it to analyze commonly observed contracts. In our model the customer (principal) faces a product availability requirement for the “uptime” of the end product. The customer then offers contracts contingent on availability to n suppliers (agents) of the key subsystems used in the product, who in turn exert cost reduction efforts and set spare-parts inventory investment levels. We show that the first-best solution can be achieved if channel members are risk neutral. When channel members are risk averse, we find that the second-best contract combines a fixed payment, a cost-sharing incentive, and a performance incentive. Furthermore, we study how these contracts evolve over the product deployment life cycle as uncertainty in support cost changes. Finally, we illustrate the application of our model to a problem based on aircraft maintenance data and show how the allocation of performance requirements and contractual terms change under various environmental assumptions.